Aesthetics philosophy of the arts - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2004)
This program presents the ideas of key figures in the shaping and understanding of aesthetic, from Plato, Francis Hutchen, and Kant to Leon Battista Alberti, Stendhal, and Tolstoy, and addresses pivotal writings, including Aristotle's Poetics and Morris Weitz's'The role of theory in aesthetics
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD Format
Keywords: Philosophy; Philosophy -- History; Aesthetics; Arts -- Philosophy